The question of validity in Vasari's art historical concept - Gibb, Barry (Rhodes University, Faculty of Humanities, Department of Fine Art, 1983)
From Introduction: Giorgio Vasari's first and second editions of his 'Lives of the Artists I appeared respectively in 1550 and 1568, just after the great period of Renaissance art in Florence and Rome had ended. As a practising Florentine architect, painter and sculptor who travelled extensively in Italy, sari could write with authority on the development of these arts throughout what he saw ~s the whole Renaissance period in that country, from the l ate 13th to the mid-16th century. Gathering information from all possible sources, his 'Lives' constitute the first comprehensive historical - critical survey of Italian Renaissance art. Much of their value resides in the first hand information they contain concerning the artists (Michelangelo in particular) who were his contemporaries, and in reflecting the aesthetic attitudes prevalent in a peak period in the history of art.
Keywords: Vasari, Giorgio, 1511-1574 -- Criticism and interpretation